Considerations of strategies to provide influenza vaccine year round. Issue 47 (25th November 2015) - Lambach, Philipp; Alvarez, Alba Maria Ropero; Hirve, Siddhivinayak; Ortiz, Justin R.; Hombach, Joachim; Verweij, Marcel; Hendriks, Jan; Palkonyay, Laszlo; Pfleiderer, Michael
Abstract: There is potential for influenza vaccine programmes to make a substantial impact on severe disease in low-resource settings, however questions around vaccine composition and programmatic issues will require special attention. Some countries may benefit from immunization programmes that provide year-round supply of vaccine; however the best way to ensure adequate vaccine supply has yet to be determined. In this report, we discuss vaccine composition, availability, and programmatic issues that must be considered when developing year-round influenza immunization programmes. We then explore how these considerations have influenced immunization practices in the Latin American region as a case study. We identify three different approaches to achieve year-round supply: (1) alternating between Northern Hemisphere and Southern Hemisphere formulations, (2) extending the expiration date to permit extended use of a single hemisphere formulation, and (3) local vaccine manufacture with production timelines that align with local epidemiology. Each approach has its challenges and opportunities. The growing data suggesting high influenza disease burden in low resource countries underscores the compelling public health need to determine the best strategies for vaccine delivery.